ASSOCIATION BETWEEN ALBUMINURIA AND SLOW GAIT SPEED IN MALES WITH TYPE 2 DIABETES - Khoo, Jonathon; Low, Serena; Lu, Tianmin; Sum, Chee Fang; Subramaniam, Tavintharan; Lim, Su Chi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
OBJECTIVES Chronic kidney disease is highly prevalent in older patients with type 2 diabetes (T2D). Albuminuria is a marker of vascular endothelial pathology that reflects increased inflammatory state of CKD. Such vascular pathology could contribute to skeletal muscle damage and poor physical performance. We aimed to investigate association between albuminuria and gait speed in males with T2D. METHODOLOGY We conducted a cross-sectional study on 100 male patients (mean age 63.3±7.3 years) with T2D. Slow gait speed was defined as ≤0.8 m/s. Albuminuria was defined as urinary albumin-to-creatinine ratio (uACR) ≥30 mg/g. Logistic regression was performed to examine relationship between albuminuria and slow gait speed, adjusting for demographics, diabetes duration, blood pressure, haemoglobin A1c, estimated glomerular filtration rate (eGFR) and appendicular skeletal muscle mass. This research has been approved by an ethics committee. RESULTS There were 51 patients with slow gait speed. The median uACR was 35 mg/g (IQR 10–174) and 50.6% of patients had albuminuria. Univariate analysis showed that albuminuria was positively associated with slow gait speed with odds ratio (OR) 2.80 (95% CI 1.20–6.57; p=0.017). The association persisted in the fully adjusted analysis with OR 4.56 (95% CI 1.24–16.77; p=0.022). Similar findings were observed using log-transformed uACR as a continuous variable with OR 1.67 (95% CI 1.19–2.36; p=0.003) in the fully adjusted analysis. There was no evidence of association between eGFR and slow gait speed. CONCLUSION Albuminuria was independently associated with slow gait speed in T2D. Hence, evaluation of albuminuria is a potential tool to identify older patients at risk of functional impairment.